2021
DOI: 10.3389/fphar.2020.616378
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin Activates the Nrf2/ARE Signaling Pathway Via Sirt1 to Improve Diabetic Renal Fibrosis

Abstract: Oxidative stress is the main factor responsible for the induction of diabetic renal fibrosis. Thus, improving the state of oxidative stress can effectively prevent the further deterioration of diabetic nephropathy (DN). Previous research has shown that formononetin (FMN), a flavonoid with significant antioxidant activity and Sirt1 activation effect, can improve diabetic renal fibrosis. However, the exact mechanisms underlying the effect of FMN on diabetic renal fibrosis have yet to be elucidated. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…SIRT1 is a NAD + sensitive deacetylase that is associated with lifespan and is believed to have beneficial effects on counter aging [ 46 ]. In addition to ameliorating insulin assistance, SIRT1 has also been known to promote the activation of the Nrf-2/ARE pathway and improve oxidative stress in diabetic nephropathy [ 47 ]. Increasing the total level and nuclear activity of SIRT1 could reduce the expression of caspase-3 and Bax and increase SOD and GSH levels in doxorubicin-induced nephropathy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is a NAD + sensitive deacetylase that is associated with lifespan and is believed to have beneficial effects on counter aging [ 46 ]. In addition to ameliorating insulin assistance, SIRT1 has also been known to promote the activation of the Nrf-2/ARE pathway and improve oxidative stress in diabetic nephropathy [ 47 ]. Increasing the total level and nuclear activity of SIRT1 could reduce the expression of caspase-3 and Bax and increase SOD and GSH levels in doxorubicin-induced nephropathy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Formononetin possesses multiple biological activities, such as antioxidant, anti-inflammatory, and regulating immune responses [ 61 , 62 ]. Formononetin improved oxidative stress and prevented the progression of renal fibrosis in DN by activating the Nrf2/ARE signaling pathway [ 43 ]. Experimental studies have shown that isorhamnetin has renoprotective effects on DN through improving fasting blood glucose, increasing autophagosomes in renal tissues, and suppressing miRNA regulation of autophagy genes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking, a method of analyzing the binding site and affinity between the conformation of molecules and macromolecular targets, has been considered a crucial technique for structure-based drug discovery [ 40 ]. The core DN-related genes targeted by the AR-PN herb pair bioactive components was identified according to the component-target-pathway network, which were further validated by molecular docking with the experimentally verified AR-PN herb pair bioactive components possessing renoprotective effects on DN, including quercetin [ 41 ], kaempferol [ 42 ], formononetin [ 43 ], and isorhamnetin [ 44 ]. First, the mol2 formats of these bioactive components were obtained from the TCMSP database and PubChem database, which were converted to the format of pdb and pdbqt via Pymol software and AutoDock Tools 1.5.6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of the mesangial cells with AGEs reduced SIRT1 protein expression and activity but induced the overproduction of fibronectin and TGF-Ī²1 levels in a dose- and time-dependent manner. SIRT1 upregulates the expression of NRF2 and activates the antioxidant response element (ARE) antioxidative pathway to prevent the progression of renal fibrosis [ 69 , 215 ]. The expression of proinflammatory and profibrotic cytokines in vitro and in vivo was reported in the HBZY-1 rat glomerular mesangial cell line treated continuously in a high-glucose milieu and in a diabetic mouse model.…”
Section: Sirt1 Expression Activity and Nad + Metab...mentioning
confidence: 99%